Relationship between Ponderal Index, Mid-Arm Circumference/ Head Circumference Ratio and Clinical Assessment of Nutritional Status Score (CANSCORE) in the Determination of Nutritional Status of Newborn at Birth in Nigeria - Bolaji, Olufunke B.; Adebami, Olusegun J.; Adebara, Olufunmilayo V.; Owa, Joshua A. (International Journal of Child Health and Nutrition, 2016)
Background: Early and accurate assessment of the nutritional status of newborns is important to many clinicians because of the potential immediate and late sequelae of malnutrition. Objective: To assess the relationship between different methods of assessing the nutritional status of neonates. Methods: Subjects were consecutive, live, singleton, full term neonates delivered in the hospital. The birth weights, Ponderal index, Mid arm circumference/head circumference ratio, birth weight for gestational age using intrauterine growth charts and Clinical Assessment of Fetal Nutritional Status Score (CANSCORE) were used to determine the nutritional status in the first 24 hours of life. Results: Of 386 subjects, 172 (44.6%) were males and 214 (55.4%) females. Nutritional status assessment using various indices showed the following prevalence of malnutrition: using birth weights, 54 (14.0%) were LBW; MAC/HC ratio showed 56 (14.5%), with PI, 64(16.6%), weight for gestational age,112(29.0%) were SGA and CANSCORE showed 90(23.3%) as malnourished among the babies.MAC/HC showed a better specificity and had a more positive correlation than PI when compared to CANSCORE whilst PI showed a better sensitivity than MAC/HC when evaluated against CANSCORE. Conclusions: Prevalence of FM is high in this study. Intrauterine growth charts and CANSCORE appeared to identify more babies with FM than other methods. CANSCORE in this study has revealed the rising trend in the prevalence of FM when compared with other studies with similar methodology. Early routine assessment of the nutritional status of newborns should be carried out so as to reduce the risk of increased morbidity and mortality associated with fetal malnutrition.